Photocatalytic and adsorption properties of TiO2-pillared montmorillonite obtained by hydrothermally activated intercalation of titanium polyhydroxo complexes - Butman, Mikhail F.; Ovchinnikov, Nikolay L.; Karasev, Nikita S.; Kochkina, Nataliya E.; Agafonov, Alexander V.; Vinogradov, Alexandr V. (Beilstein Journal of Nanotechnology, 2018)
We report on a new approach for the synthesis of TiO2-pillared montmorillonite, where the pillars exhibit a high degree of crystallinity (nanocrystals) representing a mixture of anatase and rutile phases. The structures exhibit improved adsorption and photocatalytic activity as a result of hydrothermally activated intercalation of titanium polyhydroxo complexes (i.e., TiCl4 hydrolysis products) in a solution with a concentration close to the sol formation limit. The materials, produced at various annealing temperatures from the intercalated samples, were characterized by infrared spectroscopy, differential scanning calorimetry (DSC)/thermogravimetric analysis (TGA), X-ray diffraction, dynamic light scattering (DLS) measurements, and liquefied nitrogen adsorption/desorption. The photocatalytic activity of the TiO2-pillared materials was studied using the degradation of anionic (methyl orange, MO) and cationic (rhodamine B, RhB) dyes in water under UV irradiation. The combined effect of adsorption and photocatalysis resulted in removal of 100% MO and 97.5% RhB (with an initial concentration of 40 mg/L and a photocatalyst-sorbent concentration of 1 g/L) in about 100 minutes. The produced TiO2-pillared montmorillonite showed increased photocatalytic activity as compared to the commercially available photocatalyst Degussa P25.
Keywords: adsorption; intercalation; mesoporosity; photocatalytic activity; pillared montmorillonite; titanium oxide

Nanostructured Photocatalysts: Advanced Functional Materials - Yamashita, H.; Li, H. (Springer, 2016)

(untitled) - Szczepanik, B. (Appl. Clay Sci., 2017)

Handbook of Clay Science - Vicente, M. A.; Gil, A.; Bergaya, F. (Pillared Clays and Clay Minerals, 2013)

Developments in Clay Science - Brigatti, M. F.; Galán, E.; Theng, B. K. G. (Structure and Mineralogy of Clay Minerals, 2013)

(untitled) - Kon'kova, T. V.; Alekhina, M. B.; Mikhailichenko, A. I.; Kandelaki, G. I.; Morozov, A. N. (Prot. Met. Phys. Chem. Surf., 2014)

(untitled) - Fatimah, I. (J. Mater. Environ. Sci., 2012)

(untitled) - Einaga, H. (J. Chem. Soc., Dalton Trans., 1979)

(untitled) - Bahranowski, K.; Włodarczyk, W.; Wisła-Walsh, E.; Gaweł, A.; Matusik, J.; Klimek, A.; Gil, B.; Michalik-Zym, A.; Dula, R.; Socha, R. P.; Serwicka, E. M. (Microporous Mesoporous Mater., 2015)

(untitled) - Sterte, J. (Clays Clay Miner., 1986)

(untitled) - Bernier, A.; Admaiai, L. F.; Grange, P. (Appl. Catal., 1991)

(untitled) - Zhang, G. K.; Ding, X. M.; He, F. S.; Yu, X. Y.; Zhou, J.; Hu, Y. J.; Xie, J. W. (Langmuir, 2008)

(untitled) - Chen, D.; Du, G.; Zhu, Q.; Zhou, F. (J. Colloid Interface Sci., 2013)

(untitled) - Galkina, O. L.; Vinogradov, V. V.; Agafonov, A. V.; Vinogradov, A. V. (Int. J. Inorg. Chem., 2011)

(untitled) - Xu, N.; Shi, Z.; Fan, Y.; Dong, J.; Shi, J.; Hu, M. Z.-C. (Ind. Eng. Chem. Res., 1999)

(untitled) - Sun, S.; Jiang, Y.; Yu, L.; Li, F.; Yang, Z.; Hou, T.; Hu, D.; Xia, M. (Mater. Chem. Phys., 2006)

(untitled) - Ooka, C.; Akita, S.; Ohashi, Y.; Horiuchi, T.; Szuki, K.; Komai, S.-i.; Yoshida, H.; Hattori, T. (J. Mater. Chem., 1999)

(untitled) - Kochkina, N. E.; Agafonov, A. V.; Vinogradov, A. V.; Karasev, N. S.; Ovchinnikov, N. L.; Butman, M. F. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Yoda, S.; Sakurai, Y.; Endo, A.; Miyata, T.; Otake, K.; Yanagishita, H.; Toshio, T. (Chem. Commun., 2002)

(untitled) - Damardji, B.; Khalaf, H.; Duclaux, L.; David, B. (Appl. Clay Sci., 2009)

(untitled) - Damardji, B.; Khalaf, H.; Duclaux, L.; David, B. (Appl. Clay Sci., 2009)

(untitled) - Martínez-Ortiz, M. J.; Fetter, G.; Domínguez, J. M.; Melo-Banda, J. A.; Ramos-Gómez, R. (Microporous Mesoporous Mater., 2003)

(untitled) - Ooka, C.; Yoshida, H.; Suzuki, K.; Hattori, T. (Microporous Mesoporous Mater., 2004)

(untitled) - Kaneko, T.; Shimotsuma, H.; Kajikawa, M.; Hatamachi, T.; Kodama, T.; Kitayama, Y. (J. Porous Mater., 2001)

(untitled) - Sahel, K.; Bouhent, M.; Belkhadem, F.; Ferchichi, M.; Dappozze, F.; Guillard, C.; Figueras, F. (Appl. Clay Sci., 2014)

(untitled) - Zheng, Y.; Shi, E.; Li, W.; Chen, Z.; Zhong, W.; Hu, X. (Sci. China, Ser. E: Technol. Sci., 2002)

Introduction to Zeolite Science and Practice - Schoonheydt, R. A.; Jacobs, K. Y. (Studies in Surface Science and Catalysis, 2001)

(untitled) - Zuo, S.; Ding, M.; Tong, J.; Feng, L.; Qi, C. (Appl. Clay Sci., 2015)

(untitled) - Ding, Z.; Zhu, H. Y.; Lu, G. Q.; Greenfield, P. F. (J. Colloid Interface Sci., 1999)

(untitled) - Spurr, R. A.; Myers, H. (Anal. Chem., 1957)

(untitled) - Blanco, C.; González, F.; Pesquera, C.; Benito, I.; Mendioroz, S.; Pajares, J. A. (Spectrosc. Lett., 1989)

(untitled) - Baraton, M.-I. (Open Nanosci. J., 2011)

(untitled) - Kurian, M.; Sugunan, S. (Indian J. Chem., 2003)

The Infrared Spectra of Minerals - Farmer, V. C. (Mineralogical Society, 1974)

(untitled) - Ninness, B. J.; Bousfield, D. W.; Tripp, C. P. (Colloids Surf., A, 2003)

(untitled) - Castellano, F. N.; Stipkala, J. M.; Friedman, L. A.; Meyer, G. J. (Chem. Mater., 1994)

(untitled) - Vasconcelos, D. C. L.; Costa, V. C.; Nunes, E. H. M.; Sabioni, A. C. S.; Gasparon, M.; Vasconcelos, W. L. (Mater. Sci. Appl., 2011)

(untitled) - Djellabi, R.; Ghorab, M. F.; Cerrato, G.; Morandi, S.; Gatto, S.; Oldani, V.; Di Michele, A.; Bianchi, C. L. (J. Photochem. Photobiol., A: Chem., 2014)

(untitled) - Nikitin, Yu. I.; Petasyuk, G. A. (J. Superhard Mater., 2008)

(untitled) - Sing, K. S. W.; Everett, D. H.; Haul, R. A. W.; Moscou, L.; Pierotti, R. A.; Rouquérol, J.; Siemieniewska, T. (Pure Appl. Chem., 1985)

(untitled) - Cool, P.; Zhu, H. Y.; Cassiers, K.; Vansant, E. F. (Stud. Surf. Sci. Catal., 2004)

Handbook of Layered Materials - Auerbach, S. M.; Carrado, K. A.; Dutta, P. K. (Marcel-Dekker Inc., 2004)

(untitled) - Chen, D.; Zhu, Q.; Zhou, F.; Deng, X.; Li, F. (J. Hazard. Mater., 2012)

Crystal Growth - Buckley, H. E. (John Wiley & Sons, 1951)

(untitled) - Lagergren, S. (K. Sven. Vetenskapsakad. Handl., 1898)

(untitled) - Ho, Y. S.; Mckay, G. (Can. J. Chem. Eng., 1998)

(untitled) - Weber, W. J.; Morris, J. C. (J. Sanit. Eng. Div., Am. Soc. Civ. Eng., 1963)

(untitled) - Allen, S. J.; McKay, G.; Khader, K. Y. H. (Environ. Pollut. (Oxford, U. K.), 1989)

(untitled) - Ho, Y. S.; McKay, G. (Process Biochem. (Oxford, U. K.), 1999)

(untitled) - Azizian, S. (J. Colloid Interface Sci., 2004)

(untitled) - Giles, C. H.; Smith, D.; Huitson, A. (J. Colloid Interface Sci., 1974)

(untitled) - Rangabhashiyam, S.; Anu, N.; Nandagopal, M. S. G.; Selvaraju, N. (J. Environ. Chem. Eng., 2014)

(untitled) - Petkovska, M. (Adsorption, 2014)

(untitled) - Alsawat, M.; Altalhi, T.; Shapter, J. G.; Losic, D. (Catal. Sci. Technol., 2014)

(untitled) - Yan, M.; Chen, F.; Zhang, J.; Anpo, M. (J. Phys. Chem. B, 2005)

(untitled) - Son, H.-J.; Wang, X.; Prasittichai, C.; Jeong, N. C.; Aaltonen, T.; Gordon, R. G.; Hupp, J. T. (J. Am. Chem. Soc., 2012)

Dash-Salakhly Bentonite Deposit (Establishment and Development Prospects) - Nasedkin, V. V.; Shirinadze, N. A. (GEOS, 2008)